Meeting the Kyoto targets: The importance of developing country participation - Zhong Xiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper investigates the implications of progressively broadening the scope of the market of tradable permits from no emissions trading to full global trading. We start with the no emissions trading case where each Annex I country must individually meet its Kyoto targets. Next, we consider a case where trading of emissions permits is limited to Annex I countries only. We then expand the scope of the market to include all the non-Annex I countries but China. Finally, to investigate the role China plays in bringing down Annex I countries' compliance costs, we further broaden the market to include China into full global trading. Our results clearly demonstrate that the gain of the OECD as a whole increases as the market expands. Our results also show that developing countries themselves benefit from such an expansion too because it not only provides them for additional financial resources, but also helps to cut their baseline carbon emissions by a big margin. By contrast, the former Soviet Union tends to become worse off as the market expands. The potential conflict of interest between the former Soviet Union and developing countries underlines the importance of establishing clear rules of procedure about admitting new entrants before emissions trading begins.
Keywords: Q28; Q25; Q48; Q43; 330; Emissions trading; clean development mechanism; greenhouse gases; marginal abatement costs; price of permits; Umweltabkommen; Emissionshandel; Lizenz; Entwicklungsländer; Welt; Emissionshandel